Association Between Household Cooking Fumes Exposure and Lung Cancer Risk; Brief Review and Recommendation - Kwonchul Ha; Sangjun Choi; Kyung Ehi Zoh; Dong-Hee Koh; Naeun Lee; Boowook Kim; Dong-Uk Park (Aerosol and Air Quality Research)
Abstract This study aims to summarize the main findings of meta-analyses on the association between exposure to cooking fumes CF and lung cancer risk. Meta-analyses of CF exposure and lung cancer risk published up to December 2024 were collected using PubMed and Google. Studies on lung cancer risk among cooks were also included. Study type, country, sample size, exposure surrogates, and main outcomes were summarized. A total of 293 mostly case-control studies, the bulk of which were conducted in China, were pooled into 14 individual meta-analyses. All studies showed that non-use of exhaust ventilation and use of coal for cooking significantly increased the odds ratios for lung cancer, although the odds ratios (ORs) and level of significance varied among CF exposure surrogates. However, no other cooking-related variables, such as cooking method, have shown a consistent association or causal relationship with lung cancer. Future studies should differentiate among CF exposure factors, such as the use of solid fuels, cooking methods and occupational cooking, by frequency and duration to clarify sources of CF exposure, distinguish between household and occupational CF exposure, and assess associations with lung cancer and other health outcomes. Graphical Abstract